Development of technology of pulverized coal injection in Ukraine’s blast furnaces in variable liquid and gas dynamic conditions - Semenov, Yu.S.; Shumelchyk, Ie.I.; Horupakha, V.V. (Фундаментальные и прикладные проблемы черной металлургии, 2018)
The aim of the work is to study the features of the use of pulverized coal (PCI) in the conditions of the blast furnace (BF) No. 5 of Metinvest Holding Ltd (Ukraine).